Multi-objective Cooperative Capacity Determination Method for Integrated System of Wind, Photovoltaic and Storage of Smelting Enterprises Requiring Energy Saving and Carbon Reduction - Wenguang ZHU; Wei WANG; Bin OUYANG; Hua ZHANG; Xin WANG; Rui MA (Zhongguo dianli)
Considering the uncertainty of new energy and the carbon emissions of users, a multi-objective capacity determination optimization method for energy storage of smelting enterprises considering economy and cleanliness is proposed. A two-layer energy storage optimization model is established, in which the upper layer model optimizes the energy storage configuration for large users in smelting industry who have installed or plan to install new energy power generation, and the lower layer model optimizes the timing output of energy storage. Firstly, based on the charging and discharging characteristics of wind, photovoltaic and storage, a random uncertainty model of wind and photovoltaic output and a charging and discharging model of energy storage are constructed respectively. Then, a carbon emission accounting model of smelting industry is established to calculate the total carbon emissions and carbon emissions generated by power consumption according to the user output and power load, and the corresponding carbon reduction strategy is given. And then, based on the cost of potential carbon emissions, the maximum economic benefits and minimum cost and total carbon emissions are set as multi-objectives, and the optimal energy storage capacity of enterprises is obtained under the constraints of system safe operation. Finally, taking a copper smelting enterprise as an example, the proposed method is used to optimize the energy storage capacity under the access of wind and photovoltaic with ladder capacity. The simulation results have verified the effectiveness of the proposed method.